THE IMPACT OF THE DEMOGRAPHIC CHARACTERISTICS OF THE POPULATION ON ESTIMATES OF THE COEFFICIENTS OF RADIOGENIC RISK IN THE RUSSIAN POPULATION - A. T. Gubin; V. I. Red’ko; V. A. Sakovich (Радиационная гигиена)
The aim of this work was to determine the validity of the direct transfer of the recommendations of the ICRP on the nominal risk coefficients and tissue weighting factors in a future revision of the national Radiation Safety Standards (NRB). The article compares the background age and sex distribution, and morbidity and mortality rates of the nominal population, the ICRP used to develop the latest fundamental recommendations, with appropriate indicators for the populations of Russia and Japan as the main source of data for assessment of radiogenic risk in the second half of the last decade. It is revealed that the functions of survival and age-related morbidity and mortality of the Russian population, especially for males, is significantly different from the composite population, while for the Japanese population, the differences are relatively small. The estimates of radiogenic risk coefficients for cancers of various localization using calculation schemes and risk models of the ICRP Publication 103, but based on background data on incidence and mortality of the Russian population were obtained. Baseline incidence and mortality for the Russian population are worse compared to the composite population. Hence, risk coefficients for the Russian population can be taken lower than the recommended ICRP by approximately 20% for the total population and 30% for the persons of working ages. The results clearly demonstrate the inconsistency of the modern criteria of radiation protection, based almost exclusively on the account of carcinogenic effects of ionizing radiation, since it implies that radiation is more harmful for a healthier population. The results also show timeliness of issue of the choice of the calendar period for which the age-dependence of the intensity of cancer incidence and mortality from all causes are taken into account. The article justified the continuation of the discussion of the raised issues, as well as the issues of development the mathematical models used in the estimation of radiogenic risks.